Applications Introduction to Angklung Padaeng Interactive Based Augmented Reality - Astuti, Anggi Dwi (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2022)
Angklung is a traditional musical instrument typical of West Java that must always be preserved. Currently, public awareness of the angklung musical instrument is very minimal, this is due to the lack of media introduction to the angklung musical instrument. This study aims to build angklung recognition application that uses Augmented Reality (AR) technology. The musical instrument that is the focus of this research is the Padaeng Angklung or modern angklung with a melody type made for the Android platform. To test the level of acceptance of the application that has been built, testing is carried out using the System Usability Scale (SUS) method. From the answers of 45 respondents, an average score of 78 was obtained, where in terms of the Acceptability Range of the Padaeng Angklung application it was included in the Acceptable category, in terms of the Grade Scale it was included in the Grade C position, the Adjective Rating included in the Good position and the assessment with Precentile Rank on the results. the average score of 78 lies in Grade B.